2010
DOI: 10.1140/epje/i2010-10553-y
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of ferroelectric nanoparticles immersed in a nematic liquid crystal

Abstract: A large number of interesting phenomena related to the insertion of colloidal particles in liquid crystals (LC) have recently been reported. Here, we investigate effects caused by the addition of spherically shaped ferroelectric nanoparticles to a nematic liquid crystal. Using molecular dynamics (MD) simulations, the density of LC molecules, the orientational order parameter, and the polar and azimuthal angle profiles are calculated as functions of the distance to the center of the immersed nanoparticle for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The system's reduced temperature was kept constant at T * = k B T /ε iso = 0.9, where T is the absolute temperature and k B is the Boltzmann constant. The value prescribed for T * is well below the bulk nematic-to-isotropic transition temperature, T * NI = 1.05, obtained for a similar model system [21].…”
Section: A Molecular Dynamics Simulationsmentioning
confidence: 55%
“…The system's reduced temperature was kept constant at T * = k B T /ε iso = 0.9, where T is the absolute temperature and k B is the Boltzmann constant. The value prescribed for T * is well below the bulk nematic-to-isotropic transition temperature, T * NI = 1.05, obtained for a similar model system [21].…”
Section: A Molecular Dynamics Simulationsmentioning
confidence: 55%
“…In order to understand this phenomenon and predict how to enhance it further, we investigate the isotropic-nematic transition using the free energy of Eq. (16).…”
Section: Transition Temperaturementioning
confidence: 99%
“…A distribution of published journal papers along with major research highlights over the 2003–2017 periods are schematically shown in Figure 2 (published papers: 2003—[ 15 , 16 , 17 ]; 2004—[ 18 , 19 ]; 2005—[ 20 , 21 , 22 , 23 , 24 ]; 2006—[ 25 , 26 , 27 , 28 ]; 2007—[ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; 2008—[ 37 , 38 , 39 ]; 2009—[ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]; 2010—[ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; 2011—[ 60 , 61 , 62 , 63 , 6...…”
Section: Liquid Crystals Doped With Ferroelectric Nanoparticles: Amentioning
confidence: 99%